The presence of B-cell activating factor (BAFF) in umbilical cord blood in both healthy and pre-eclamptic pregnancies and in human breast milk - Bienertova-Vasku, Julie; Zlamal, Filip; Tomandl, Josef; Dostálová, Zuzana; Novak, Jan; Splichal, Zbynek; Ventruba, Pavel; Thon, Vojtech; Vasku, Anna (Journal of reproductive immunology, 2015)
B-cell activating factor (BAFF) is an important immune regulator that was recently reported to be secreted by placenta. The aim of the study was to investigate the presence of BAFF in umbilical cord blood, maternal serum, and breast milk in normal and in pre-eclamptic pregnancies. Pairs of maternal serum/umbilical cord blood were obtained from 12 pre-eclamptic and 34 physiological pregnancies. Another cohort of 10 healthy lactating women was established that was followed up for 6 months following delivery to investigate BAFF levels in breast milk. BAFF levels in maternal peripheral blood were significantly higher in physiological pregnancies than in pre-eclamptic pregnancies (p < 0.03). Furthermore, we observed a consistent presence of BAFF in breast milk during the 6-month post-partum period of breastfeeding. In this study, we demonstrate that BAFF levels are significantly lower in maternal peripheral blood in pre-eclamptic pregnancies. We also report the consistent presence of BAFF in breast milk in healthy women. More research into the role of BAFF in pregnancy, and during breastfeeding, is imperative.
Keywords: těhotenství; B-Cell Activating Factor; Pre-Eclampsia; Pregnancy; dospělí; fetální krev; Female; mateřské mléko; Humans; Milk, Human; Postpartum Period; Adult; preeklampsie; ženské pohlaví; Fetal Blood; faktor aktivující B-buňky; poporodní období; lidé